Population Policy in Government Politics from The Utstman Time to The Recep Tayyib Erdogan Period in Raising Turkey Islamism - Ihwan Ihwan; Muzani Jalaludin; Muhammad Zid (Budapest International Research and Critics University, 2022)
Population policy in government politics is dynamic from time to time. This study was conducted to answer the question of how the population policy in the political field of government in Turkey from the Ottoman period to the time of Recep Tayyib Erdogan built Turkey as a country with an Islamic pattern. This research uses descriptive qualitative methods and secondary data from books, journals, articles, and the internet to answer this question. Turkey stands on the ruins of the Ottoman Empire, which ruled for nearly six centuries (1342-1924 AD). The Ottoman Empire reached its peak during the reign of Suleiman Akanuni. The Ottoman Empire was utterly ruined at the end of the early 19th century. During 1924-1928, the government of Mustafa Kemal tried to abolish all institutions and symbols that referred to traditional Islam, which are considered to hinder the modernization of Turkey. In 1983, democracy in Turkey was restored. Erdogan's domestic political policies include: (a) Freeing education fees and (b) Erdoan reinstating the old habit of teaching the Koran and Hadith in public schools. (c) The policy requires Islamic religious education from primary and secondary school to 12 levels. This is the new face of Turkey under Erdogan's political management